3-Equitable Prime Cordial Labeling of Standard Splitting Graphs - Philomena, V. Sharon; Kavya, B (International Journal of Computer Sciences and Engineering, 2025)
A 3-equitable prime cordial labeling is extension of prime cordial labeling .Splitting graph S^` (G) was introduced by Sampath Kumar and Walikar. For a graph G the splitting graphS` of G is obtained by adding a new vertex v` corresponding to each vertex v of G such that N(v)=N(v^` ). In this paper we prove the splitting graph of cycleC_n, path P_n, bistar B_(n,n) and wheel W_n admits 3-equitable prime cordial labeling.